Promoting the Increase of Mathematical Representative Skill in Vocational Students through Blended Problem-Based Learning - Sri Rahayu Setiyorini; Azalina Nurul Fajariah (IKIP Siliwangi, 2019)
Low mathematical representation skill causes the inability of vocational students solving problems creatively as demanded by industries. Researches showed that blended problem-based learning (BL-PBL) combining online and offline learning to train students to independently solve problems was proven to increase mathematical skills in education levels other than vocational school. Therefore, this research aimed to evaluate BL-PBL effect to mathematical representation skill escalation in vocational high school. Quantitative study with pre-test and post-test control group design was performed to two randomly-chosen classes over vocational schools in Kabupaten Bandung Barat, West Java, Indonesia. Samples were divided into two groups: experimental (BL-PBL method) and control (lecture method). Initial skill was determined by pre-test while learning outcome was determined using post-test. Data was analysed by t-test and two-way ANOVA with 0.05 significance level using IBM SPSS. Result showed the initial skill of two groups was similar. After treatment, N-gain data uncovered a significant increase of representative skill in experimental group. While, two-way ANOVA test showed no interaction between learning model used and student grouping based on initial skill to representation skill. Finally, BL-PBL was proven to increase mathematical representation skill in vocational students and, hence, is suggested to be implemented in vocational high school